Ships and Diplomacy. The Historical Connection between the Letters RS 18.031 (from Tyre) and RS 94.2483 (from Ugarit) - Vita, Juan-Pablo (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2017)
The kingdom of Ugarit is famous for being both maritime and commercial in nature, features largely due to the location of the country and its physical geography. The Western border of the country is washed by the Mediterranean for a stretch of about one hundred kilometres and the natural contours of the coast facilitate access to the sea. This convergence of geographical, physical and technical factors combined with the Ugaritians aptitude for commerce in which they had invested so much, resulted in Ugarit dominating trade by land and sea in Late Bronze Age Syria.